Déficits de memória na prole decorrentes do transtorno do estresse pós- traumático perinatal e possíveis implicações neurogênicas. - Sá, Josiane Costa De (2021)
The pregnancy stress can be extremely harmful to both mother and offspring, indicating that the intrauterine environment has a significant long-term impact on the individual's life. In front of, this stress in early life can cause pathologies such as depression and anxiety in adolescence and adulthood, as well as damage to cognitive function. There are several types of stress, and stressful situations will not always trigger post-traumatic stress disorder (PTSD). The animal models for PTSD are diverse and, in the literature, there are no studies that evaluate an animal model of PTSD during the perinatal period and its cognitive impairment in the offspring. Thus, the purpose of this study is to investigate the neurogenic mechanisms associated with alterations in learning and memory in the offspring resulting from pregnancy PTSD, since the relationship between hippocampal neurogenesis and cognitive function is already well established. For this purpose, pregnant Wistar rats were used, which were induced to PTSD by paw shock, followed by social isolation. The dams were evaluated in maternal behavior, freezing behavior, and the Open Field test. The tests performed on female and male pups were: Physical Development and Reflex, Open Field, Object Recognition, and Morris Water Maze. Statistical analyses were performed using GraphPad software version 8.0. All experimental procedures were approved by the Ethics Committee on Animal Experimentation of the Federal University of Alfenas (Unifal-MG), protocol n° 50/2018. Our results indicated that the dams rats of the shock group presented reduced maternal care, memory retention to trauma and anxious-like behavior. The male pups, but not the females, showed longer time to produce the negative geotaxis reflex, exploratory hyperactivity, and 2-hour object recognition memory impairment. In the 24- hour object recognition test and the Morris Water Maze, males and females showed impairments in both. We identified and quantified some proteins involved in the memory process, such as Brain-derived Neutrophic Factor (BDNF), Doublecortin (DCX) and Synaptophysin in the hippocampus by Western Blotting. For female pups there were no differences between the groups, while male pups from stressed mothers showed a reduction in BDNF and DCX. Based on the results obtained, we conclude that gestational PTSD can generate cognitive impairment for the offspring, being possibly associated with neurogenic mechanisms; however, other mechanisms not evaluated may be responsible for cognition loss, especially in female offspring.